Exploring critical determinants of protein amyloidogenesis: a review. (19th July 2013) - Sarkar, Nandini; Dubey, Vikash Kumar
Abstract : The transformation of polypeptide chains from their globular native structure to fibrillar aggregates has been a matter of great concern because of the involvement of these aggregates in the onset of several degenerative diseases. These aggregates exhibit highly ordered cross β sheet structures and are known as 'amyloids'. Formation of amyloids in the body is associated with cytotoxicity due to direct interaction of the aggregated species with the cell membrane leading to cellular permeability or due to loss of functionality of the proteins involved in the amyloid formation. The preference of polypeptide chains to remain in their native conformation or to aggregate into amyloids is guided by several factors such as its conformation at specific condition, concentration, physicochemical properties of the amino acid sequence and so on. In the current review, we have reviewed the different factors that guide the transition of proteins from their natively folded state to the amyloidogenic state. Understanding the critical determinants of amyloidogenesis is vital towards deciphering the molecular mechanism of amyloidogenesis and for the development of effective therapeutics against amyloidosis. Copyright © 2013 European Peptide Society and John Wiley & Sons, Ltd. Abstract : Amyloids are ordered protein aggregates whose deposition leads to the onset of various degenerative neuronal and non‐neuronal diseases. Despite extensive research, the crucial factors that guide protein transition from soluble state to fibrillar‐aggregated state remain elusive. The current review article, for the first time, provides a comprehensive and systematic overview of the critical determinants in the molecular pathway(s) of amyloidogenesis.